A Nurse-Led mHealth Self-Management Program (mChemotherapy) for Breast Cancer Patients Undergoing Chemotherapy: Study Protocol of a Randomized Controlled Pilot Study. (12th July 2022) - Shi, Nuo; Wong, Arkers K. C.; Wong, Frances K. Y.; Zhang, Nan; Lai, Xiaobin; Gan, Lu
Background: The global pandemic has caused breast cancer (BC) patients who are receiving chemotherapy to face more challenges in taking care of themselves than usual. A novel nurse-led mHealth program (mChemotherapy) is designed to foster self-management for this population. The aim of the pilot study is to determine the feasibility, usability, and acceptability of an mChemotherapy program for breast cancer patients undergoing chemotherapy. The objective also is to evaluate the preliminary effects of this program on adherence to app usage, self-efficacy, quality of life, symptom burden, and healthcare utilization among this group of patients. Methods: This is a single-blinded randomized controlled pilot study that includes one intervention group (mChemotherapy group) and one control group (routine care group). Ninety-four breast cancer patients who commence chemotherapy in a university-affiliated hospital will be recruited. Based on the Individual and Family Self-management Theory, this 6-week mChemotherapy program, which includes a combination of self-regulation activities and nurse-led support, will be provided. Data collection will be conducted at baseline, week 3 (T1), and week 6 (T2). A general linear model will be utilized for identifying the between-group, within-group, and interaction effects. Qualitative content analysis will be adopted to analyze, extract, and categorize the interview transcripts. Discussions: Breast cancer patients receiving chemotherapy are a population that often experiences a heavy symptom burden. During the pandemic, they have had difficulties in self-managing the side effects of chemotherapy due to the lack of face-to-face professional support. An mChemotherapy program will be adopted through a self-regulation process and with the provision of nurse-led real-time professional support for these patients. If proven effective, BC patients who engage in this program will be more likely to take an active role in managing their symptoms, take responsibility for their own health, and subsequently improve their self-efficacy and adherence to the use of the app.